Gold and Iron Tailings to Improve the Compressive Strength and Workability of Concrete - Reyes, L. J. Chavarría-; Vallejos, C. M. Chavarry-; Rodríguez, J. S.Támara; Cano, J. W. Blas; Roque, R. M. Reyes; Vergara, E. A. Milla; Ramírez, A. E. Gómez (International Journal of Membrane Science and Technology, 2023)
This scientific study aims to determine the optimal replacement percentage of mine tailings as a substitute for fine aggregate to improve both the compressive strength and the workability of the concrete, both in the case of gold mine tailings and gold mine tailings iron. It is a documentary, bibliographical and descriptive investigation that follows a deductive method with a quantitative approach. In addition, it is descriptive, correlational, and explanatory, with a descriptive level and a non-experimental, longitudinal, and retrospective design. The results indicate that the incorporation of 15% gold mining tailings increases the compressive strength by 4,44% while incorporating 12% iron mining tailings increases the resistance to compression by 7,79%. Likewise, by adding 30% gold mining tailings, a notable increase of 74,36% in tensile strength is obtained. On the other hand, when 5% gold mine tailings are added, the slump remains at 4"; however, by increasing the addition to 10%, it decreases from 2" to 1.77". In the case of tailings iron miners incorporating 30% the settlement remains at 2"; but by increasing the amount to 12%, the slump decreases from 3.32" to 1.57". Finally, the study shows that using mine tailings as a substitute for fine aggregate can significantly improve the compressive strength and workability of concrete, depending on the type of tailings and its percentage of incorporation.